Social media and its influencers: A study of Indonesian state-defending strategy in the 21st century - Antonius Widodo; Muhammad Hadianto Wirajuda; Joni Widjayanto (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
Globalization can be seen in almost every aspect of people's lives, especially in the influence of advances in information and communication technology, including the Internet, the emergence of various social media platforms, and the rise of social media influencers in society. With the active role of social media influencers and social media penetration among Indonesian people, the Indonesian government can take advantage of this phenomenon to strengthen strategic programs called State-Defending Program. The development of the state-defending program by the MoD to enhance national defense and character needs to adapt to technological developments. Social media can answer this challenge. By optimizing the functions of social media and influencers in supporting defense governance and state defense, the MoD, as the leading sector, needs to put forward new communication strategies and methods to expand the spectrum of influence for state-defending for all levels of society in Indonesia. Finally, this study aims to analyze the development of the state-defending program and its challenges, as well as the state-defending development strategy implemented by the Ministry of Defense through social media engagement.